Electricity Crisis (Load Shedding) in Nepal, Its Manifestations and Ramifications - Shrestha, Ratna Sansar (Hydro Nepal: Journal of Water, Energy and Environment, 2011)
Nepal is in the grip of electricity crisis. The electricity crisis of this millennium began in 2006. Nepal saw the last electricity crisis of the last millennium in 1999 and with the commissioning of Khimti Hydroelectric Project in 2000, there was no load shedding until 2005. Earlier, the Nepal Electricity Authority (NEA) used to attribute load shedding to "no water in rivers." Since the last wet season, however, Nepal has suffered from load shedding even while struggling with "food" problem. With no electricity for 16 hours a day, the last dry season was the worst so far. Nepal's macro economy is suffering heavily due to this phenomenon. It is anomalous, however, that even at the time of load shedding the NEA has been spilling energy due to mismatch of system as well as transmission congestion. The NEA has promised respite from the problem in next five years, but the facts and figures do not corroborate the claim. The government of Nepal’s (GoN) defective vision and short sighted policy is at the root of the problem, one that can be mitigated by setting the vision right and making the policy more forward looking and based on the principle of self-reliance. Key words: Electricity crisis; Load shedding; NEA; IPPs; Adverse impact; Anomaly; Respite; GoN Policy; Tariff; Nepal DOI: 10.3126/hn.v6i0.4187 Hydro Nepal Vol 6, January 2010 Page : 7-17 Uploaded Date: 23 January, 2011